A Study of the Association of Parental Consanguinity with Birth Defects and Neonatal Medical Problems in Babylon Province (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
A cross-sectional study of 138 married couples and their offspring was done in Babylon Province from the period between the first of February till the end of April 201 6 .The parents; who were either consanguine or no consanguine, came from mixed urban and rural backgrounds. Socio -demographic and obstetric data were recorded. Neonatal data were extracted from the medical records of the labor and neonatal care wards. The incidence of congenital and birth defects was significantly higher for those born to consanguine parents especially for first cousin couples.  The incidence of congenital abnormalities in newborns  of all non-consanguineous parents was 7.1% as compared to 23.2 % for newborns of all consanguineous group. In addition prematurity, history of previous prenatal mortality, and low birth weight were more common in the consanguineous group.